Systemic Bevacizumab for Recurrent Respiratory Papillomatosis: A Scoping Review from 2009 to 2022 - Laura Torres-Canchala; Daniela Cleves-Luna; Oriana Arias-Valderrama; Estephania Candelo; María Angelica Guerra; Harry Pachajoa; Manuela Olaya (MDPI AG, 2022)
Background: Respiratory recurrent papillomatosis (RRP) is a fatal disease with no known cure. In severe RRP cases, systemic bevacizumab (SB) could be used as adjuvant therapy. Objective: This study aims to determine the extent and type of evidence in relation to the clinical outcomes of RRP after SB treatment. Methods: Participants with RRP of all genders are included in this scoping review. There were no exclusion criteria (country, language, or document type). The information sources included experimental, quasi-experimental, and analytical observational studies. Unpublished data will not be covered, but gray literature was covered. Screening, paper selection, and data extraction were all done by two independent reviewers. This procedure was performed blindly. Results: Of the 175 unique records found, 15 were eligible for inclusion. Fourteen studies were included after applying inclusion and exclusion criteria. Thirty-four patients in these studies came from the United States, India, Germany, Colombia, Argentina, Chile, and Spain. In total, 17 and 34 patients were below 18 years old and were adults respectively. The most commonly reported dose was 10 mg/kg, which was received by 25 (73.5%) patients. According to reports, 58.8% of patients completed the questionnaire. Twelve (35%) patients did not require a repeat surgery. The time interval between surgical procedures has increased for patients who require them. Conclusion: SB may be a promissory treatment and control option for RRP. More research is needed to evaluate the efficiency and adverse effects in various populations.